1999
DOI: 10.1103/physrevb.60.9630
|View full text |Cite
|
Sign up to set email alerts
|

Critical dynamics of a uniaxial and dipolar ferromagnet

Abstract: We study the critical dynamics of three-dimensional ferromagnets with uniaxial anisotropy by taking into account exchange and dipole-dipole interaction. The dynamic spin correlation functions and the transport coefficients are calculated within a mode coupling theory. It is found that the crossover scenario is determined by the subtle interplay between three length scales: the correlation length, the dipolar and uniaxial wave vector. We compare our theoretical findings with hyperfine interaction experiments on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…It has been suggested that muon-lattice dipolar interactions, known to strongly affect the paramagnetic critical dynamics near a magnetic transition point, could be responsible for the observed low value of the w exponent. 43,44 By considering now the short-time µSR data (see Fig. 11) we can follow the temperature evolution of the internal magnetic field, as sensed at the muon stopping sites.…”
Section: F Muon-spin Relaxationmentioning
confidence: 99%
“…It has been suggested that muon-lattice dipolar interactions, known to strongly affect the paramagnetic critical dynamics near a magnetic transition point, could be responsible for the observed low value of the w exponent. 43,44 By considering now the short-time µSR data (see Fig. 11) we can follow the temperature evolution of the internal magnetic field, as sensed at the muon stopping sites.…”
Section: F Muon-spin Relaxationmentioning
confidence: 99%
“…Though, λ is not a strict order parameter, it is a measure of spatial correlation length ξ and can give an idea of critical dynamics: λ ∼ ξ 3/2 for a ferromagnet and λ ∼ ξ 1/2 for an antiferromagnet, whereas ξ ∼ (T /T tr −1) −ν in the close vicinity of the transition temperature T tr [36- [38,40,41]. The fits of λ(T ) are shown by the solid curves in Fig.…”
Section: Muon Spin Relaxation Studymentioning
confidence: 99%
“…The third remarkable feature is the thermal behavior of Z which is not unlike the one found for the metallic ferromagnets Fe, Ni, Gd, and GdNi 5 at ambient pressure: [44][45][46] the relaxation rate is found to saturate when approaching T C .…”
Section: Spin-lattice Relaxation Ratementioning
confidence: 99%